G‐SIMS analysis of organic solar cell materials. (12th September 2014) - Franquet, A.; Fleischmann, C.; Conard, T.; Voroshazi, E.; Poleunis, C.; Havelund, R.; Delcorte, A.; Vandervorst, W.; Lee, Yeonhee; Moon, DaeWon; Kang, Hee Jae; Kim, Kyung Joong; et al.
<x xml:space="preserve">Abstract</x> Interpretation of time‐of‐flight (TOF)‐SIMS spectra of organic molecules could be difficult because of the presence of a high number of secondary ion peaks; this often requires the use of data analysis methods to simplify the TOF‐SIMS measurements. In this study, we will demonstrate that the gentle‐SIMS method could be applied to more easily interpret the TOF‐SIMS spectra of organic solar cell materials. Various conditions of the primary ion beam were used to generate the gentle‐SIMS spectra from pure layers of two materials, i.e. PC70BM and PCDTBT. It will be shown that by using specific conditions of the primary ion column, the corresponding molecular ion or characteristic peaks of the pure organic materials are highlighted. Results obtained on an organic layer prepared from a mixture of both materials will be also discussed. Copyright © 2014 John Wiley & Sons, Ltd.